1993
DOI: 10.1111/j.1600-0528.1993.tb00716.x
|View full text |Cite
|
Sign up to set email alerts
|

A panoramatomographic study of the teeth and jaws of Finnish university students

Abstract: A random sample of panoramic radiographs was taken of 1027 (386 male and 641 female) university students. All the students were born between 1965 and 1971. The following were examined: caries, apical radiolucencies, endodontically treated teeth, marginal and vertical bone loss, third molars, supernumerary, missing, and persisting teeth, bone structure, condyles, maxillary sinuses and soft tissue calcifications. In the inter- (of two examiners) and intra-examiner variation Kappa indices varied between 0.15 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 20 publications
2
15
1
1
Order By: Relevance
“…The etiology of transmigration is unknown; however, abnormal displacement of the tooth bud or deviation during development is the most commonly accepted explanation. 23 Although unerupted maxillary canine is seen almost 20 times more frequent than mandibular canines, it is interesting that TCs are more common in the mandible 3 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The etiology of transmigration is unknown; however, abnormal displacement of the tooth bud or deviation during development is the most commonly accepted explanation. 23 Although unerupted maxillary canine is seen almost 20 times more frequent than mandibular canines, it is interesting that TCs are more common in the mandible 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, maxillary incisors radices are longer than mandibular incisor roots and the short distance between the base of the nose and apices of the incisors , which makes the transmigration more difficult 3,18 . Finally, it has been suggested that the most important factor in maxillary canine transmigration is their positions and angulations 13 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Literatürde %6,9'dan %76,6'ya kadar gömülü kalma sıklıkları belirtilmiştir. [24][25][26][27][28][29] Genellikle sırasıyla; üçüncü molarlar, maksiller kaninler, maksiller santral dişler ve premolar dişler gömülü olarak en fazla rapor edilen dişlerdir. [30][31][32][33] Özellikle üçüncü molar dişlerin gö-mülü kalmasına bağlı olarak oluşan çeşitli rahatsız-lıkların, diş sinir ilişkisinin, diş pozisyonun, bukkal ve linguale komşuluklarının cerraha yol göstermesi açı-sından KIBT imajlarının değerlendirilmesi gerekir.…”
Section: Bulgularunclassified